Le potentiel des hautes terres de l'Afrique de l'est pour la production de lait - Tendances economiques. Produits laitiers - International Livestock Centre for Africa (1979)
Description of the highlands of East Africa and study on production systems in the ILCA study areas, particularly traditional systems of farming; w. data on ILCA research programmes and the first results obtained at debre zeit farm.